Dilemma of gonial angle measurement: Panoramic radiograph or lateral cephalogram - Radhakrishnan, Pillai Devu (Imaging Sci Dent, 2017)
PURPOSE: The purpose of this study was to evaluate the accuracy of panoramic imaging in measuring the right and left gonial angles by comparing the measured angles with the angles determined using a lateral cephalogram of adult patients with class I malocclusion. MATERIALS AND METHODS: The gonial angles of 50 class I malocclusion patients (25 males and 25 females; mean age: 23 years) were measured using both a lateral cephalogram and a panoramic radiograph. In the lateral cephalograms, the gonial angle was measured at the point of intersection of the ramus plane and the mandibular plane. In the panoramic radiographs, the gonial angle was measured by drawing a line tangent to the lower border of the mandible and another line tangent to the distal border of the ascending ramus and the condyle on both sides. The data obtained from both radiographs were statistically compared. RESULTS: No statistically significant difference was observed between the gonial angle measured using the lateral cephalograms and that determined using the panoramic radiographs. Further, there was no statistically significant difference in the measured gonial angle with respect to gender. The results also showed a statistically insignificant difference in the mean of the right and the left gonial angles measured using the panoramic radiographs. CONCLUSION: As the gonial angle measurements using panoramic radiographs and lateral cephalograms showed no statistically significant difference, panoramic radiography can be considered in orthodontics for measuring the gonial angle without any interference due to superimposed images.